A brief history of pharmacy admissions in North America. (November 2019) - Davis, Erin; Braha, Richard; McAlorum, Shannon; Kelly, Debbie
The move from a Bachelor of Science in Pharmacy to a Doctor of Pharmacy degree, both in the United States and in Canada, has been accompanied by a general move towards increased prepharmacy admission requirements and longer pharmacy programs. Historically, the most thoroughly researched pharmacy admissions variables include grade point average (GPA), Pharmacy College Admissions Test (PCAT), interviews and critical thinking tests. Most programs now require a combination of academic (GPA ± PCAT) and nonacademic characteristics (e.g., interviews, volunteering, critical thinking tests, essays). This review focuses on GPA and the PCAT as academic admissions measures and the interview (both traditional and the multiple mini-interview) and critical thinking tests as nonacademic measures. There is evidence that prepharmacy GPA, the PCAT and admissions interviews are correlated with academic success in a pharmacy program. Repeating a prepharmacy course is a negative predictor of academic success. The multiple mini-interview and various critical thinking tests have been studied in pharmacy admissions, but the evidence to date does not support their use for predicting success. Several areas require further research, including finding an effective measure of reasoning and critical thinking skills. The relationship between admission test scores and clinical performance also requires further study, as academic achievement in pharmacy programs has been the main measure of success to date.